Dichotomy between high quality education and Islamic cultural literacy among Muslim graduates from the west - Zakariyah, Luqman (2013)
Despite Huntington’s claim of clash of civilization and refutation of this claim by many respondents, Muslims countries still admirably adore the quality assurance guaranteed in Western education system without heeding to the dearth of Islamic cultural literacy (ICL). Cultural literacy has taken different interpretations aftermath Hirsch exposition of the concept in later 1990s. Thus, Islamic cultural literacy in this paper denotes fundamental principles underpinning Islamic ethics in acquiring knowledge. It indicates familiarity of the graduates with the core courses and approaches in studying Islam and Muslims. This paper aims to critically appraise the impact of quality assurance in British higher education on Islamic cultural literacy to the Muslim graduates from those universities. It preliminary asserts that though, Muslim graduates from Western universities might be privileged to be employed due to material inclination of the world order, they are less privileged of Islamic cultural literacy.